Memaknai pendidikan Karekter dalam Pemikiran Ibn Miskawaih - Zaimudin Zaimudin (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
The basic potential (the talent and capacity) of human that will develop optimally if process of education and environment appropriate affectively and eficient. This process of education and environmental are the basis of educational thought Ibn Miskawayh based on the moral development of welded with various scientific of the world and the hereafter. In the theoretical framework, needs to be built theory of middle way from a variety of extreme in order to take the maximum benefit for the creation of Insan al-Kamil because his soul rising from the lowest level to the highest heading of the psych the human being (al-nafs al-insaniyah). For that we need a method of education that is appropriate to the application in accordance with the circumstances of psychology learners. It’s to empowering this human characters needs capitalized with a variety of knowledges and sciences in accordance with the talent and capacity of learners. The sciences are offered ranging from religious sciences, social sciences, and natural sciences, and technology even in enhanching competitiveness in the global competition.